THE INTEREST OF THE UNITED STATES OF AMERICA TOWARDS THE "GLOBAL RECALL" PRODUCT OF TOYOTA AUTOMOBILE MANUFACTURE IN THE COUNTRY - Ardhian Yoedistira Putra (2011)
The issue towards massive Recall on 8.5 million of Toyota's vehicles in range of 2009 until 2010 years in United States arose many questions and consequences. The domino effect suddenly happened to the other Japanese Automakers in United States. The other Japanese Automakers such as Honda, Mitsubishi, Mazda, and another one are perforce to Recall their units because some certain problem. In case of Toyota, the issue firstly blew up in the early 2009 because of gas pedal, break, trapping mat diso